Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ptr.5890
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antitubercular Activity of 3‐Deoxysappanchalcone Isolated From the Heartwood of Caesalpinia sappan Linn.

Abstract: Responsible for nearly 1.5 million deaths every year, the infectious disease tuberculosis remains one of the most serious challenges to global health. The emergence of multidrug-resistant tuberculosis and, more recently, extensively drug-resistant tuberculosis poses a significant threat in our effort to control this epidemic. New drugs are urgently needed to combat the growing threat of antimicrobial resistance. To achieve this goal, we screened approximately 500 species of medicinal plant methanol extracts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Seo et al reported that the 3-deoxysappanchalcone isolated from the heartwood of C. sappan Linn. possessed the antitubercular activity of both drug susceptible and drug resistant of MTB strain H 37 Rv [12]. Based on these facts, this study was conducted to determine anti-MTB strain H 37 Rv and iron chelation activities of SWE.…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al reported that the 3-deoxysappanchalcone isolated from the heartwood of C. sappan Linn. possessed the antitubercular activity of both drug susceptible and drug resistant of MTB strain H 37 Rv [12]. Based on these facts, this study was conducted to determine anti-MTB strain H 37 Rv and iron chelation activities of SWE.…”
Section: Introductionmentioning
confidence: 99%
“…The main active substance isolated from the heartwood of that plant is 3-deoxysappanchalcone, which displays activity not only against M. tuberculosis, but also against multidrugresistance and extensively drug-resistance tuberculosis strains. The MIC is within the range 3.125-12.5 µg/ml, which is much higher than rifampicin in most cases [13]. Diterpenoids, as the researchers have discovered, possess some anti-mycobacterial properties.…”
Section: Extracts and Natural Substances Isolated From Plantsmentioning
confidence: 91%
“…The extract has been used extensively as a natural dye, especially in the textile industry due to its low toxicity and low cost [37]- [39]. Sappanwood extracts in addition to functioning as a natural red dye, also show great benefits as antibacterial agents [38], [40]- [42], antioxidants [38], [43]- [45], and pharmacological activity [46]. Also, braziline is easily oxidized by light to form a very red brazilein [35], [38].…”
Section: Introductionmentioning
confidence: 99%